(3TQM cJGH GdQMeI dLGHQ Hf MjGfs - (3GdWZQGFis; (3CHh ehSi,J (B200 (3g` s
(3ChdgG (B:s
(3hHYO deG cKQJ fYeI Gddg YR hLd Ydi ajeG aJMg Ydi hgOGfi dg ef GdYde s
(3BNQgG (B:s
(3adjcf gPG BNQ GdcdGe ajg hCfG CfTO Gddg JYGdi ef hbY Ydjg gPG GdcJGH hGWdY Ydi eG ajg Cf jYed ajg HWGYI Gddg JYGdi s
(3Vef eLehY , JQJjHgG (B: (3ef U (B196 - (3U(B213s
(3GdfSNI HgG MhGTs
(3cJH GdfGSN GdhQb GdChd SGbW ef GdefJSNs
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
(3JHUQI GdYfhGf (B:s
(3TQMs
Keywords: (3GdcjejGA h GdWHjYjGJs